(untitled) (Modern Problems of Metallurgy, 2024)
The dimensions of the rolled products are affected by various factors that lead to fluctuations in the thickness and length of the rolled products and the appearance of bars of normal length when cutting on saws, therefore the issue of increasing the accuracy of the dimensions of the rolled products is always relevant. Direct devices for measuring the thickness of rolled shaped profiles of a complex cross-sectional shape are complex computer complexes that have a high cost. The purpose of the study is to study the possibility of controlling the dimensions of rolled products using indirect methods of assessing changes in the thickness of rolled products. For this purpose, a study was carried out on the measurement of the length of rolled products using a length meter, which is based on the principle of measuring the length of rolled products by the rotation of the rolls. Studies of the meter's operation have shown that the use of a microcontroller for processing the measurement results allows to increase the accuracy of the roll length measurement. This happens by taking into account the slippage of the rolls relative to the rolling stock during metal capture and by averaging the number of pulses, which falls on the basic distance of the photosensors. Comparison of the measurement results with the actual length of the rolled product confirmed the possibility of using this device for measuring the length of the rolled product in the flow. When studying the rolling process, the length of the rolls after the finishing stand, the temperature of the rolls before the finishing stand, the thickness and the motor current of the main drive of the finishing stand were measured. The measured results showed the presence of a low-frequency component of these parameters, which is associated with the wear of bearings and roll gauges, which leads to an increase in the thickness of the rolled products. The wear of bearings is not a stationary process, so the compensation of the effect of wear on the dimensions of rolled steel should be performed according to the measurement results, and not randomly or as a function of time. Calculating the average values of rolled length, motor current, and rolled temperature makes it possible to evaluate the change in rolled thickness due to the wear of bearings and roll gauges and to compensate for its influence on the dimensions of rolled products in a timely manner.